Personality types, perceived job-related stress and coping strategies among hotel front line employees / Nurshazliza Shaiful Kahar and Hassnah Wee. - Shaiful Kahar, Nurshazliza; Wee, Hassnah (Universiti Teknologi MARA Cawangan Selangor, 2020)
This paper aims to investigate personality types, perceived job-related stress, and coping strategies among hotel front line employees. This study used a survey to investigate demographics and the key variables in the research framework. Data analysis is based on 326 hotel front line employees’ feedback employed at 4-star and 5-star hotels in Selangor. The results revealed that personality types and perceived job-related stress have significant relationship, and coping strategies moderate the relationship between personality types and perceived job-related stress. The outcome of this study perhaps could help hotel managers in establishing efficient stress management in order to care for the organisation and its employees.